Understanding TBI as a Risk Factor Versus a Means of Suicide Death Using Electronic Health Record Data. Issue 2 (3rd April 2023) - Rossom, Rebecca C.; Peterson, Edward L.; Chawa, Mansi Sethi; Prabhakar, Deepak; Hu, Yong; Yeh, Hsueh-Han; Owen-Smith, Ashli A.; Simon, Gregory E.; Williams, L. Keoki; Hubley, Samuel; Lynch, Frances; Beck, Arne; et al.
Abstract: Objective: The aim of this research was to examine predictors and characterize causes of suicide death in people with traumatic brain injury (TBI) and conduct sensitivity analyses with and without people whose first diagnosis of TBI occurred within 3 days of their suicide death. Methods: This case-control study examined suicide risk for people with TBI in eight Mental Health Research Network–affiliated healthcare systems. Sample 1 included 61 persons with TBI who died by suicide and their 75 matched controls with TBI who did not die by suicide between January 1, 2000, and December 31, 2013. Sample 2 excluded the 34 persons with TBI whose first TBI diagnosis occurred within 3 days of their suicide death and their 46 matched controls. Descriptive statistics characterized the sample stratified by cases and controls, while conditional logistic regression models estimated the adjusted odds of suicide. Results: Over half of suicide deaths occurred within 3 days of a person's first diagnosis of TBI in the larger sample. After excluding these persons, people with TBI were 2.84 (95% confidence interval [CI]: 2.15–2.73) times more likely to die by suicide than were people without TBI. Among those with TBI, men were 16.39 times (95% CI: 1.89–142.15) more likely to die by suicide than were women. Conclusions: Accounting for TBI as a potential consequence of suicide attenuates the association between TBI and suicide, but a robust association persists—especially among men. Ultimately, all people with TBI should be carefully screened and monitored for suicide risk. HIGHLIGHTS: People with traumatic brain injury (TBI) were at considerably elevated risk for suicide death Men with TBI had significantly increased risk of suicide death compared to women with TBI TBI timing suggests confusion of risk factors for and consequences of suicide